2020
DOI: 10.1371/journal.pone.0228561
|View full text |Cite
|
Sign up to set email alerts
|

Completing Linnaeus’s inventory of the Swedish insect fauna: Only 5,000 species left?

Abstract: Despite more than 250 years of taxonomic research, we still have only a vague idea about the true size and composition of the faunas and floras of the planet. Many biodiversity inventories provide limited insight because they focus on a small taxonomic subsample or a tiny geographic area. Here, we report on the size and composition of the Swedish insect fauna, thought to represent roughly half of the diversity of multicellular life in one of the largest European countries. Our results are based on more than a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…We also attempted to estimate species richness using extrapolation via frequency ratio [ 62 ] and combined non-parametric estimators (CNE) [ 63 ], with the former being widely used to estimate microbial diversity [ 64 , 65 ]. Both estimators suggest that mangroves are even more species-rich than rainforest and swamp forest habitats (Additional file 2 : Figure S4) with coastal- and urban forests yielding even higher estimates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also attempted to estimate species richness using extrapolation via frequency ratio [ 62 ] and combined non-parametric estimators (CNE) [ 63 ], with the former being widely used to estimate microbial diversity [ 64 , 65 ]. Both estimators suggest that mangroves are even more species-rich than rainforest and swamp forest habitats (Additional file 2 : Figure S4) with coastal- and urban forests yielding even higher estimates.…”
Section: Resultsmentioning
confidence: 99%
“…The habitat type “mangrove” was treated both as a single habitat as well as separate sites (PU, SB, SMN, SMO, others) in separate analyses. We also obtained species richness extrapolations for each habitat using a frequency ratio estimator [ 62 ] and a combined non-parametric estimator (CNE) [ 63 ] based on combined Chao1 and Chao2 extrapolations. Both were performed in R, with the former using the breakaway package and the latter using R code published with the original manuscript.…”
Section: Methodsmentioning
confidence: 99%
“…Our knowledge of species diversity in insects is still embarrassingly incomplete, even in relatively well-known regions such as Europe. A large inventory based on millions of insect specimens from the Swedish Malaise Trap Project (SMPT) recently concluded that the largest gaps in our knowledge are among dipteran decomposers and hymenopteran parasitoids (Ronquist et al 2020), such as Ichneumonidae Latreille, 1802 (also called "Darwin wasps" since recently: Klopfstein et al 2019). Even small and easily recognized genera still hold undetected diversity, if examined carefully.…”
Section: Introductionmentioning
confidence: 99%
“…Although our results are based on one month's sampling in 2018, it is strikingly similar in overall taxonomic composition to the multiyear national assessment for Sweden based on Malaise traps. Similar to SMTP, we also find most of the new species detected belong to Diptera and Hymenoptera [39]. However, our approach is much quicker and covers a much larger geographical area.…”
Section: Discussionmentioning
confidence: 54%